Management Of Postpartum Blues With Mothers Experiencing Sadness (Depression) About Their Babies In Postpartum Mothers - Riswanti Riswanti; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
ABSTRACT Postpartum blues is a mild emotional disorder often experienced by mothers after childbirth, characterized by feelings of sadness, anxiety, crying spells, and mood swings. This condition can impact the mother's psychological health and the baby's care process if not properly managed. This study aims to determine the management of postpartum blues in postpartum mothers experiencing sadness or depression about their babies. This study used a quantitative approach with a descriptive analytical design. The sample consisted of 35 postpartum mothers selected using a purposive sampling technique. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire and observation sheets. Data were analyzed using univariate and bivariate analyses with the Chi-square test. The results of the study showed that most mothers experienced mild to moderate postpartum blues. Factors influencing postpartum blues include lack of family support, hormonal changes, physical exhaustion, and anxiety in caring for a baby. Effective management includes emotional family support, health education, counseling, and assistance from healthcare professionals. The statistical test results showed a p-value of 0.003 (p < 0.05), indicating a significant effect of postpartum blues management on the psychological well-being of mothers after childbirth. It was concluded that proper management of postpartum blues can help reduce the level of sadness and depression in mothers after giving birth and improve the mother's ability to care for her baby. Keywords: Postpartum Blues, Postpartum Depression, Postpartum Mothers, Maternal Mental Health, Family Support